Experiences of overseas nurse educators teaching in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Doctorate of Education at Massey University, Palmerston North, New Zealand - Skaria, Reen Thankachen (Massey University, 2017)
Globalisation and a shortage of registered nurses in New Zealand have caused an increase in the number of overseas registered nurses and nurse educators migrating to New Zealand. This phenomenological study explored the experiences of overseas nurse educators teaching in New Zealand using van Manen’s approach to hermeneutic phenomenology. The lived experiences of 17 overseas nurse educators were explored through in-depth interviews, and phenomenological analytical procedures were utilised to bring to light the hidden layers of meaning inherent within these experiences. The study revealed that overseas nurse educators initially experienced a sense of non-belonging in New Zealand, while their separation from their homeland and migration to a new country resulted in a sense of disorientation. They experienced both physical and emotional separation from their loved ones. Integration was the preferred method of adaptation to New Zealand among the study participants. However, they wanted to choose which aspects of the new culture they would adopt and to what extent they would adapt. A lack of preparation and a lack of suitable orientation programmes prolonged the adaptation process of overseas nurse educators. Time was a crucial factor for overseas nurse educators’ adjustment to the New Zealand setting. Adjustment problems were greatest at the start. However, their lives improved over time as they overcame the challenges they faced. Positive relationships had a positive impact on overseas nurse educators’ adaptation to New Zealand. Adjustment was dependent on the quality and quantity of the support received.
Keywords: Nurse educators; Foreign workers; Acculturation; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::Nursing education